Pengaruh Ekstrak Daun Bengkuang (Pachyrrhizus Erosus) Terhadap Kematian Larva Aedesaegypti Spp - Agus Muslih; Dadang Kuswandi Jalari (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2013)
Aedes aegypti mosquito is a vector of Dengue Hemorrhagic Fever (DHF), which until now a public health problem in Indonesia. One of the efforts made in combating vector of dengue is by controlling the Aedes aegypti larvae mosquito using larvacide. Biological larvacide derived from plants have the potential to control mosquito larvae, besides that its use is safe for humans. One biological larvacide that can be used is from yam leaves (Pachyrrhizus erosus). From past research that yam leaf extract (Pachyrrhizus erosus) can kill mosquito larvae Anopheles aconitus with concentration 2.8771% on LC50. Research aims to determine the extent of yam leaf extract (Pachyrrhizus erosus) can kill mosquito larvae of Aedes aegypti in different levels of concentration. As the dependent variable in this study was the death of the Aedes aegypti mosquito larvae with the independent variable is the variation of the concentration yam leaf extract (Pachyrrhizus erosus). Samples were Aedes aegypti mosquito larvae in instar Ill / IV were relatively stable from outside influence as much as 30 larvae for each treatment. Treatment in this study using yam leaf extract solution concentration respectively 2.0%, 4.0%, 6%, 8% and 10%, with 4 repetitions and an untreated control. The statistical analysis used in this study is analisaregresi probit with SPSS 17 for windows. Probit analysis of the test results demonstrate the effective concentration at the LC50, LC90 and LC95 with confidence intervals (SK) is acceptable, namely 95%, respectively were 6.314%, 10.104% and 11.179% with upper and lower limits. From this analysis the bias is known, the higher the concentration of leaf extract Yam, the higher the mortality rate of larvae of Aedes aegypti until it reaches the maximum limit larvae mortality.